Photoluminescence Origin of Zero-Dimensional Cs4PbBr6 Perovskite - Wang, Liangling; Liu, Hong; Zhang, Yuhai; Mohammed, Omar F (ACS energy letters, 2020)
Green-emitting zero-dimensional perovskite Cs4PbBr6, consisting of an array of isolated [PbBr6]4– octahedra, has drawn a magnitude of interest due to its peculiar yet robust photoluminescence properties. Given many advances in the past few years, the true nature of the unusual green emission from a wide-bandgap Cs4PbBr6 remains elusive. Although a number of reviews have been published on this subject, the emerging evidence motivates us to summarize the rapid progress about the debate, whereby critical comments were made to either rationalize or question each point of view. This Review summarizes the latest findings on the PL origins covering both CsPbBr3 impurity and defect theories. Specifically, the chemical nature of the defects, including Br vacancies, polybromide, self-trapped excitons, and interstitial molecules, is discussed. The phase transformation between CsPbBr3 and Cs4PbBr6 is particularly stressed because it has brought more cloud on the PL puzzle. Finally, we discuss the potential application of this material and envisioned several future directions that may clarify the mechanism of PL.